2009
DOI: 10.1002/adfm.200800822
|View full text |Cite
|
Sign up to set email alerts
|

Kinetically Controlled Synthesis of Hexagonally Close‐Packed Cobalt Nanorods with High Magnetic Coercivity

Abstract: High‐quality monodisperse metallic cobalt nanorods are obtained by the reduction of carboxylate salts of CoII in 1,2‐butanediol using a rapid, simple, and solid‐template‐free procedure. In this polyol process, particle shape can be controlled via the growth rate, which depends on three parameters: i) the nature of the cobalt carboxylate, ii) the temperature ramp, and iii) the basicity of the medium. Cobalt in the hexagonally close‐packed phase favored the growth of anisotropic particles. Magnetic measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
131
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(138 citation statements)
references
References 40 publications
(18 reference statements)
6
131
0
1
Order By: Relevance
“…[5,13,24]. This method has shown an accurate size control of the nanoparticles via the kinetic control of the growth step (author?)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,13,24]. This method has shown an accurate size control of the nanoparticles via the kinetic control of the growth step (author?)…”
Section: Methodsmentioning
confidence: 99%
“…Since the development of a wide range of synthesis routes for the elaboration of controlled nano-objects, the number of studies trying to understand the zoology of the magnetic properties showed by these systems is continuously increasing [1][2][3][4][5][6][7][8][9]. Among them, Cobased anisotropic nanomaterials are attracting a great part of scientific interest mainly for their possible applications as nanomagnets in (nano)medicine [10] and recording media [11], and as building blocks in high energy nanostructured bulk magnets [12].…”
Section: Introductionmentioning
confidence: 99%
“…Such wires can be produced either by electrochemical deposition of metals in uniaxial porous templates such as anodic aluminium oxide (Fert et al 1999), by organo--metallic synthesis (Wetz et al 2007), or by the polyol process (Ung et al 2007;Soumare et al 2008 andSoumare et al 2009). Such wires exhibit specific magnetic properties owing to their large shape anisotropy (Sellmyer et al 2001 andMcGary et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt nanowires synthesized by reduction in liquid polyol are mono--crystalline and mono--disperse (Soumare 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Nanosized transition metal particles with extremely large surface areas invite special focus in the material design, because when effective particle size (also the shape and surface topology) decreases below a certain *Corresponding author. Email: kalyanchem@dmrl.drdo.in critical value useful properties are significantly altered from the bulk values [8,9]. Synthesis of cobalt in shape of nanoparticles (Co-NPs) with specific crystal structure and shapes such as rods or wires is a challenging task because cobalt assumes three near iso-energetic allotropes, namely, face-centered cubic (fcc), hexagonal close-packed (hcp) and epsilon crystal structures.…”
Section: Introductionmentioning
confidence: 99%